A Molecular Phylogeny of Plesiorycteropus Reassigns the Extinct Mammalian Order ‘Bibymalagasia’ - Buckley, Michael (Public Library of Science, 2013)
Madagascar is well known for its diverse fauna and flora, being home to many species not found anywhere else in the world. However, its biodiversity in the recent past included a range of extinct enigmatic fauna, such as elephant birds, giant lemurs and dwarfed hippopotami. The ‘Malagasy aardvark’ (Plesiorycteropus) has remained one of Madagascar’s least well-understood extinct species since its discovery in the 19(th) century. Initially considered a close relative of the aardvark (Orycteropus) within the order Tubulidentata, more recent morphological analyses challenged this placement on the grounds that the identifiably derived traits supporting this allocation were adaptations to digging rather than shared ancestry. Because the skeletal evidence showed many morphological traits diagnostic of different eutherian mammal orders, they could not be used to resolve its closest relatives. As a result, the genus was tentatively assigned its own taxonomic order ‘Bibymalagasia’, yet how this order relates to other eutherian mammal orders remains unclear despite numerous morphological investigations. This research presents the first known molecular sequence data for Plesiorycteropus, obtained from the bone protein collagen (I), which places the ‘Malagasy aardvark’ as more closely related to tenrecs than aardvarks. More specifically, Plesiorycteropus was recovered within the order Tenrecoidea (golden moles and tenrecs) within Afrotheria, suggesting that the taxonomic order ‘Bibymalagasia’ is obsolete. This research highlights the potential for collagen sequencing in investigating the phylogeny of extinct species as a viable alternative to ancient DNA (aDNA) sequencing, particularly in cases where aDNA cannot be recovered.